Digestive enzyme activity and food ingesta in juvenile shrimp Litopenaeus vannamei (Boone, 1931) as a function of body weight - Gamboa Delgado, Julián; Molina Poveda, César; Cahu, Chantal (Wiley-Blackwell, 2003)
A study was conducted to evaluate variations of digestive enzyme activities in Litopenaeus vannamei (Boone) reared in commercial ponds under semi-intensive conditions. Shrimp were collected at each body weight increase of 2 g. As the shrimp grew (2^12 g), signi¢cant increases in the activities of lipase and chymotrypsinwere observed. The total protease activity decreased from 6 g onwards. Trypsin activity showed a peak at 6 g and amylase activity increased two-fold after 2 g. Additionally, the stomach contents were analysed microscopically for shrimp between 2 and 10 g. Plant matter contributed above 30% of the total stomach content in 6-, 8- and 10-g shrimp. Detritus represented 58% and 62% of the total stomach content in 2- and 4-g shrimp, respectively, decreasing to 33^43% at greater shrimp weights. Arti¢cial feed showed amaximumcontribution of 20% in 6-g shrimp. The present results show changes in the enzyme activity after the shrimp reach 6 g in body weight, evidenced by a decrease in total protease and an increase in lipase and amylase activities. The amylase/protease ratio was 2.6 in 2-g shrimp and increased steadily to 9.6 in 12-g shrimp. These ¢ndings suggest an adaptation of the enzymatic activity to diets with lower protein content as body weight increases, and may be related to the variation of the di¡erent items found in the stomach.